2019
DOI: 10.3389/fendo.2019.00340
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism and Depression: A Systematic Review and Meta-Analysis

Abstract: Background: Thyroid function is closely associated with neuropsychological functions, including mental state and cognitive functions. Although thyroid function is routinely examined in persons with depressive symptom, the association between subclinical hypothyroidism (SCH) and depression remains inconclusive. Objective: This systematic review and meta-analysis aimed to evaluate the risk of depression in persons with SCH. Methods: The PubMed, Embase, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 44 publications
1
23
1
4
Order By: Relevance
“…Drawing on a sample of children and adolescents affected by HYPO SC , Cerbone et al ( 8 ) found no relationship between HYPO SC and mental health, which is supported by results of the present study as well as the two most recent meta-analyses of the relationship between HYPO SC and depression in adults ( 73 , 74 ). Tang et al ( 74 ) showed in a subgroup analysis that only adults aged 50 and above were more likely to experience depression which agrees with considerations by Dayan and Panicker ( 75 ), arguing that an underlying chronic condition, more likely to occur in the elderly, could be the cause of increased rates of depression in adults rather than HYPO SC . This suggestion is plausible since there is no known physiological mechanism by which HYPO SC would cause significant effects on HRQoL and mental health in the presence of peripheral euthyroidism and without concurrent thyroid autoimmunity.…”
Section: Discussionsupporting
confidence: 87%
“…Drawing on a sample of children and adolescents affected by HYPO SC , Cerbone et al ( 8 ) found no relationship between HYPO SC and mental health, which is supported by results of the present study as well as the two most recent meta-analyses of the relationship between HYPO SC and depression in adults ( 73 , 74 ). Tang et al ( 74 ) showed in a subgroup analysis that only adults aged 50 and above were more likely to experience depression which agrees with considerations by Dayan and Panicker ( 75 ), arguing that an underlying chronic condition, more likely to occur in the elderly, could be the cause of increased rates of depression in adults rather than HYPO SC . This suggestion is plausible since there is no known physiological mechanism by which HYPO SC would cause significant effects on HRQoL and mental health in the presence of peripheral euthyroidism and without concurrent thyroid autoimmunity.…”
Section: Discussionsupporting
confidence: 87%
“…The association between subclinical thyroid dysfunction and depressive symptoms is unclear because studies to date have yielded conflicting results. Several studies showed that participants with subclinical hypothyroidism or subclinical hyperthyroidism had more severe depressive symptoms, but other studies reported no differences [7][8][9][10][11][12][13][14][15] . The largest prospective study published showed no association between subclinical hypothyroidism and incidence of depression after 2 years of follow-up 16 , whereas depressive symptoms were associated with subclinical hyperthyroidism (but not subclinical hypothyroidism) in another prospective study 11 .…”
Section: Abbreviationsmentioning
confidence: 99%
“…Odds for incidence of depression were not higher for participants with subclinical hyperthyroidism than * Analysis adjusted for depressive symptoms at baseline, sex, age, and education (The CHS, Health ABC Study, and the InChianti Study were additionally adjusted for income). † Analysis includes the same studies as for the primary outcome analysis: Leiden 85+ (9), PROSPER (7), Health ABC Study (40), CHS (26), InChianti Study (41), HUNT (42). ‡ Analysis includes the same studies as in the primary outcome analysis except of HUNT (42).…”
Section: Subclinical Hyperthyroidismmentioning
confidence: 99%
“…No relevant difference was found between subclinical hypothyroidism or hyperthyroidism and euthyroid controls in the most recent study by Wildisen et al, in 2020 (7), in which 23,038 participants from six prospective cohort studies were analyzed. However, other trials have shown a positive correlation between subclinical hypothyroidism and depression (8,9). The current study (5) provides more data about this critical question.…”
Section: Commentarymentioning
confidence: 75%